MnBr2-catalyzed direct and site-selective alkylation of indoles and benzo[h]quinoline - Jagtap, Rahul A.; Verma, Suryadev K.; Punji, Benudhar (Organic Letters, 2020)
Manganese-catalyzed regioselective C-H alkylation of indoles and benzo[h]quinoline with a variety of unactivated alkyl iodides is reported. Unlike other Mn-catalyzed C-H functionalization, this protocol does not require a Grignard reagent base and employs a simple and inexpensive MnBr2 as a catalyst. This method tolerates diverse functionalities, including fluoro, chloro, bromo, iodo, alkenyl, alkynyl, pyrrolyl, and carbazolyl groups. The alkylation proceeds through a single-electron transfer pathway comprising reversible C-H manganesation and involving an alkyl radical intermediate.

Manganese-catalyzed C(sp(2))-H alkylation of indolines and arenes with unactivated alkyl bromides - Verma, Suryadev K.; Punji, Benudhar (Chemistry-an Asian Journal, 2022)
Selective C(sp(2))-H bond alkylation of indoline, carbazole and (2-pyridinyl)arenes with unactivated alkyl bromides is achieved using MnBr2 catalyst in the absence of an external ligand. The alkylation uses a simple LiHMDS base and avoids the necessity of Grignard reagent, unlike other Mn-catalyzed C-H functionalization. This reaction proceeded either through a five- or a less-favored six-membered metallacycle, and tolerated diverse functionalities, including alkenyl, alkynyl, silyl, aryl ether, pyrrolyl, indolyl, carbazolyl and alkyl bearing fatty alcohol and polycyclic-steroid moieties. Alkylation follows a single electron transfer (SET) pathway involving 1e oxidative addition of alkyl bromide and a rate-limiting C-H metalation.
Keywords: Alkylation; C-H activation; indoline; ligand-free; manganese